Pluralism or Fragmentation?: The Twentieth-Century Employment Law Regime in Canada - Fudge, Judy; Tucker, Eric (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2000)
Abstract In 1947, Bora Laskin, the doyen of Canadian collective bargaining law, remarked that "Labour relations as a matter for legal study... has outgrown any confinement to a section of the law of torts or to a corner of the criminal law. Similarly, and from another standpoint, it has burst the narrow bounds of master and servant." That standpoint was liberal pluralism, which comprises collective bargaining legislation administered by independent labour boards and a system of grievance arbitration to enforce collective agreements. After World War II, it came to dominate our understanding of labour relations law such that, according to Laskin, reference to "pre-collective bargaining standards is an attempt to re-enter a world that has ceased to exist." But this picture is only partially true. Instead of replacing earlier regimes of industrial legality, industrial pluralism was grafted on to them. Moreover, it only encompassed a narrow, albeit crucial, segment of workers; in the mid-1950s "the typical union member was a relatively settled, semi-skilled male worker within a large industrial corporation." More than 65 per cent of Canadian workers at that time, a large proportion of whom were women and recent immigrants, fell outside the regime. This paper broadens the focus from collective bargaining law to include other forms of the legal regulation of employment relations, such as the common law, minimum standards, and equity legislation. In doing so, it examines the extent to which liberal pluralism regime was implicated in constructing and reinforcing a deeply segmented labour market in Canada. It also probes whether the recent assaulton trade union rights may be the trajectory for the reconstruction of a new regime of employment relations.